The Clinical Relevance of IL-17-Producing CD4+CD161+ Cell and Its Subpopulations in Primary Sjögren’s Syndrome - Linbo Li; Jing He; Lei Zhu; Yuqin Yang; Yuebo Jin; Rulin Jia; Xu Liu; Yanying Liu; Xiaolin Sun; Zhanguo Li (Journal of Immunology Research)
Objective. Th17 cells have been demonstrated to play an important role in the onset and development of primary Sjögren’s syndrome (pSS). In this study, we evaluated the expansion and clinical significance of circulating CD4+CD161+ T cell and its “effector” (CD4+CD25−CD161+ T cell) and “regulatory” (CD4+CD25+CD161+ T cell) subpopulations. Methods. Fifty-eight pSS patients and 16 healthy controls (HCs) were recruited in our study. The cell populations and intracellular IL-17 expression were analyzed by flow cytometry. The disease activity was evaluated by the EULAR-SS Disease Activity Index (ESSDAI). Autoantibodies were measured by ELISA or indirect immunofluorescence assay. Results. The CD161+ T cell fractions showed higher proportions of IL-17-producing cells. The frequencies of the overall CD4+CD161+ T cell population and its effector subset were positively correlated with disease activity parameters and more severe disease manifestations. A significant elevation of the CD4+CD25+CD161+ T cell subpopulation was observed in the peripheral blood of pSS patients compared to HCs and this subset showed decreased regulatory functions compared with the CD4+CD25+CD161− population. Conclusion. Circulating CD4+CD161+ T cell populations associated with pSS disease activity and severity. These cells might be involved in the development of pSS and could be potential therapeutic targets in the treatment of pSS.